1988
DOI: 10.1152/ajpgi.1988.254.4.g552
|View full text |Cite
|
Sign up to set email alerts
|

Digestive motor patterns and transit of luminal contents in canine ileum

Abstract: In the present study ileal motor patterns caused by orally administered noncaloric and nutrient meals were investigated. Effects of nutrients were additionally elucidated by an ileal infusion of nutrients. Conscious dogs equipped with closely spaced extraluminal transducers were used. Motor patterns were quantified by a computerized method. Transit rates were measured fluoroscopically. Compared with the motor pattern caused by the noncaloric meal, the nutrient meal diminished the number of contractions from 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The relative proportions of these three patterns and the switches between them determine the rate of transport of the contents along the intestine and hence the efficacy of the digestive and absorptive processes [4], [5], [6]. They depend at least in part on the nutrients within the intestinal content [5], [7], [8]. However, the mechanisms by which food and the derived nutrients drive this critical motor function and the underlying neural activity remain ill-defined at best.…”
Section: Introductionmentioning
confidence: 99%
“…The relative proportions of these three patterns and the switches between them determine the rate of transport of the contents along the intestine and hence the efficacy of the digestive and absorptive processes [4], [5], [6]. They depend at least in part on the nutrients within the intestinal content [5], [7], [8]. However, the mechanisms by which food and the derived nutrients drive this critical motor function and the underlying neural activity remain ill-defined at best.…”
Section: Introductionmentioning
confidence: 99%
“…Postprandially, the MMC is disrupted by a pattern of irregular contractions that mixes the ingesta with digestive juices and facilitates the exposure of luminal contents to the bowel wall (18) (28). Small intestinal transit, which is slowed postprandially (35), is related to the length of pressure waves (31), indicating that the organization of contractions is an important determinant of luminal flow. More recently, Rayner et al (23) have reported that small intestinal glucose absorption may depend on duodenal motor activity in diabetics (23).…”
mentioning
confidence: 99%
“…Dietary lipids initiate a feedback reflex that converts the propagative to the non-propagative motility pattern that characterizes the fed state [21,22]. Many diverse lipid substances are capable of activating the ileal brake, including triglycerides, phospholipids, and long-and short-chain non-esterified fatty acids (NEFA) [23,24], requiring lipase activity [24].…”
Section: Dietary Fatmentioning
confidence: 99%